Asuhan Keperawatan Jiwa Pada Pasien Isolasi Sosial Menarik Diri di RSKD Dadi Provinsi Sulawesi Selatan Tahun 2024 - Febrina Dwiyanti; Sartika Sartika; Nurhijrani Nurhijrani; Didin Wahyudi (Fatiakara Care: Jurnal Ilmiah Keperawatan, 2025)
Social isolation is a situation where an individual experiences a decline or even is completely unable to interact with others around him. Social isolation patients experience disturbances in interaction and experience behavior of not wanting to communicate with others around them, preferring to stay silent, shut themselves up, and avoid others. The results of the initial data on April 4, 2024, according to data from the Dadi Hospital of South Sulawesi Province, show that the number of psychiatric patients obtained in 2023 from June-December is 841 while in 2024 from June-February there are 1092 patients. So that the total number of patient data throughout 2023-2024 amounted to 1,933 people. The purpose of this study is to apply psychiatric nursing care to clients with social isolation with the stages of the nursing process (Assessment, Diagnosis, Planning, Implementation and Evaluation of Nursing). The results of the study after conducting nursing care with patient 1 (Mrs. H) and patient 2 (Mrs. R) with the problem of social isolation: withdrawing, it was obtained that patient 1 and patient 2 could be confident again in what was in her body and the patient had the desire to go home immediately and return soon gathering with their families, and after being given the care of the patient's assistance, the patient responds to be able to carry out activities according to the abilities he still has on a sustainable basis for the advancement of the patient's ability.